Teaching foreign languages to the primary school students involving poetry to the classes - Xoliqov, Farxod; Majidova, Gulrukh (Maktabgacha taʼlim jurnali, 2021)
Literary activity has a huge impact on teaching foreign languages for both categories of linguistic skills such as receptive skills including reading and listening and productive skills such as speaking and writing.